Attenuated Psychotic Symptoms in Adolescents With Chronic Cannabis and MDMA Use - Wiedmann, Melina; Kuitunen-Paul, Sören; Basedow, Lukas A.; Roessner, Veit; Golub, Yulia (Frontiers in Psychiatry, 2022)
Objectives: Both substance use, on the one hand, and the first signs of psychosis, on the other, commonly begin in adolescence. Adolescents with substance use disorder (SUD) frequently show recreational use of cannabis and 3,4‐methylenedioxymethamphetamine (MDMA). When attenuated psychotic symptoms (APS) occur during the course of SUD, they are commonly attributed to the cannabis use, neglecting the role of other substances abused, such as MDMA in the risk of psychosis. Methods: We analyzed retrospective self-reports on APS (Prodromal Questionnaire, PQ-16) and amount of cannabis and MDMA use in n = 46 adolescent psychiatry outpatients with SUD. N = 17 (35%) individuals reported MDMA consume additional to cannabis. Furthermore, we examined the associations of APS with cannabis and MDMA use in stepwise hierarchical regressions while controlling for trauma history, birth complications and gender. Results: APS were not related to cannabis- (B = 0.04, p = .842), but to MDMA use (B = 4.88, p = .001) and trauma history (B = 0.72, p = .001). Gender (B = -0.22, p = .767) and birth complications (B = -0.68, p = .178) were not associated with APS. Discussion: Our results indicate that MDMA use additional to cannabis use is associated with APS among adolescent SUD patients. Contrary to our expectations, we did not see an association of cannabis use and APS. We speculate that cannabis increases the risk for psychosis after a longer period of use and in combination with other risk factors, such as trauma history. Clinicians should screen for APS among SUD patients using MDMA and cannabis in order to adapt treatment plans of SUDs. Future research should validate these findings in longitudinal studies including polysubstance use and trauma history.